God, She is Beautiful... The Disturbing Representation of Women in Hannah and her Sisters - Hilaria Loyo (Miscelánea: A Journal of English and American Studies)
This paper discusses the ideological scope of Woody Allen's Hannah and  Her Sisters (1986) in relation to gender and sexual difference within  American postmodernism —the cultural phenomenon in which Woody Allen  has been inscribed. The analysis uses a theoretical framework derived from  feminist film theory and focuses mainly on visual representation and its  enunciative process. More particularly, the analysis centres on the  representation of women within the film as well as on its intertextual aspects,  that is, its parodic allusions and references to other films, generic influence,  and stardom. The final aim is to account for the unresolved ambivalence  manifested in the representation of women in this film.